2003
DOI: 10.2527/2003.812545x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen metabolism and recycling in Holstein heifers12

Abstract: To study the effect of dietary N level on urea kinetics and recycling, four Holstein heifers (267 +/- 3.6 kg) were used in a Youden square design. Isocaloric diets with a N content of 1.44, 1.89, 2.50, 2.97, and 3.40% were fed at approximately 1.8 times maintenance intake. Increasing the N content of the diet increased urinary N excretion (P < 0.001) and N balance (P < 0.01), but did not affect the fecal N excretion (P = 0.21). Increasing the level of dietary N, increased urea production (P < 0.001) and excret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

45
216
11
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(278 citation statements)
references
References 25 publications
45
216
11
6
Order By: Relevance
“…In cattle-fed diets >12% of CP, the amount of N recycled (g/d) through the rumen wall may be relatively constant (Marini and Van Amburgh, 2003;Maltby et al, 2005;Reynolds and Kristensen, 2008). Nevertheless, in the current analysis, amount of urea N recycled were linearly associated with increases of N intake, with the increases in recycling accounting for about 35% of increases in N intake.…”
contrasting
confidence: 49%
See 3 more Smart Citations
“…In cattle-fed diets >12% of CP, the amount of N recycled (g/d) through the rumen wall may be relatively constant (Marini and Van Amburgh, 2003;Maltby et al, 2005;Reynolds and Kristensen, 2008). Nevertheless, in the current analysis, amount of urea N recycled were linearly associated with increases of N intake, with the increases in recycling accounting for about 35% of increases in N intake.…”
contrasting
confidence: 49%
“…The UUE:TUN may indicate the priority for excretion of excess N in relation to muscle mass, muscle growth or perhaps acid-base regulation (Huntington and Archibeque, 1999). Considering a broad range of dietary CP, UUE:TUN in ruminants increases with dietary CP concentration (Lapierre and Lobley, 2001;Marini and Van Amburgh, 2003;Reynolds and Kristensen, 2008;Wickersham et al, 2008). In accordance with these authors, we observed that UUE:TUN ASD = asymptotic SD of the relationship; UER = urea N entry rate (g/BW 0.75 ); CP = dietary CP concentration (% of dry matter); UER:NI = UER to N intake ratio (g UER/ g N intake); UUE = urinary urea N elimination (g/BW 0.75 ); UUE:UER = urinary urea N elimination relative to entry rate of urea N (g UUE/g UER); UUE:TUN = urinary urea N elimination relative to total urinary N excretion (g UUE/g TUN); GER = gastrointestinal entry rate of urea N (g/BW 0.75 ); ROC:GER = urea N re-entry to ornithine cycle relative to gastrointestinal entry rate of urea N (g ROC/g GER); UFE:GER = urea N to fecal excretion relative to gastrointestinal entry rate of urea N (g UFE/g GER); MNU = microbial incorporation of recycled urea N (g/BW 0.75 ); NI = N intake (g/BW 0.75 ); MNU:GER = microbial incorporation of recycled urea N relative to gastrointestinal entry rate of urea N (g MNU/g GER); CP:DOM = ratio between dietary CP and digestible organic matter concentrations (g CP/kg digestible organic matter).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that dietary fibre increased excretion of endogenous N resulting from increased mucosal cell turnover when high-fibre diets were fed to rats (42) . Besides, a negative relationship exists between urea recycling to the intestine and NI (43,44) . In the present analysis, intakes of DM and digestible OM were similar among FL-0, FL-L and FL-H diets.…”
Section: Endogenous Nitrogen Lossesmentioning
confidence: 99%